2023
DOI: 10.18632/aging.204780
|View full text |Cite
|
Sign up to set email alerts
|

FBXO28 promotes proliferation, invasion, and metastasis of pancreatic cancer cells through regulation of SMARCC2 ubiquitination

Songbai Liu,
Peng Liu,
Changhao Zhu
et al.

Abstract: The E3 ligase F-box only protein 28 (FBXO28) belongs to the F-box family of proteins that play a critical role in tumor development. However, the potential function of FBXO28 in pancreatic cancer (PC) and its molecular mechanism remain unclear. In this study, we examined FBXO28 expression in PC and its biological role and explored the mechanism of FBXO28-mediated proliferation, invasion, and metastasis of PC cells. Compared with paracancerous tissues and human normal pancreatic ductal epithelial cells, FBXO28 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…It has been established that SWItch/sucrose non-fermentable (SWI/SNF) is a tumor suppressor that regulates epithelial-mesenchymal transition [26,27]. Moreover, SMARCC2 is the core subunit of the SWI/SNF complex[28], which is prone to mutation in various malignant cancers, resulting in low expression levels [29,30]. Our investigation unveiled SMARCC2 as a potential interacting partner of TRIM37 through CO-IP assays and mass spectrometry.…”
Section: Discussionmentioning
confidence: 73%
“…It has been established that SWItch/sucrose non-fermentable (SWI/SNF) is a tumor suppressor that regulates epithelial-mesenchymal transition [26,27]. Moreover, SMARCC2 is the core subunit of the SWI/SNF complex[28], which is prone to mutation in various malignant cancers, resulting in low expression levels [29,30]. Our investigation unveiled SMARCC2 as a potential interacting partner of TRIM37 through CO-IP assays and mass spectrometry.…”
Section: Discussionmentioning
confidence: 73%
“…Meanwhile, self-degradation of FBXO28 is observed [ 31 ]. Interestingly, FBXO28 is found to exert either oncogenic or tumor suppressing functions by targeting MYC, SMARCC2 or HIF-1α, under different cellular contexts, complicating its role in tumorigenesis and metastasis [ 12 , 13 , 32 ]. Here, we identify SNAI2 as a novel substrate of FBXO28 based on the following lines of evidence: (1) FBXO28 interacts with SNAI2 under endogenous and exogenous conditions; (2) cellular levels and protein half-life of SNAI2 are increased or decreased by FBXO28 depletion or FBXO28 overexpression, respectively, without affecting its transcriptional expression; (3) FBXO28-SNAI2 binding results in K48-linked SNAI2 polyubiquitination, which is abrogated by FBXO28ΔF mutant, although the mutant fails to rescue SNAI2 by a separately transcriptional mechanism yet to be identified; (4) given that PKA inhibitors abrogate the FBXO28-SNAI2 binding and FBXO28-mediated SNAI2 degradation, our data suggested that PKA could be a kinase that phosphorylates putative S158, S247 and S254 residues at the SNAI2’s binding motif and facilitate its binding to and subsequently degradation by FBXO28.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the public databases, FBXO22, FBXO28, and FBXO45 are highly expressed in PDAC and correlated with poor prognosis in patients (Zhang et al, 2021a). FBXO28 contributes to the proliferation of PDAC by promoting ubiquitin-mediated degradation of SMARCC2 (Liu et al, 2023a), and FBXO45 facilitates cell proliferation by ubiquitinating USP49 through binding to its SPRY domain (Wu et al, 2022a).…”
Section: E3s and Dubs Regulate Cell Proliferation In Pdacmentioning
confidence: 99%
“…Based on the public databases, FBXO22, FBXO28, and FBXO45 are highly expressed in PDAC and correlated with poor prognosis in patients ( Zhang et al, 2021a ). FBXO28 contributes to the proliferation of PDAC by promoting ubiquitin-mediated degradation of SMARCC2 ( Liu et al, 2023a ), and FBXO45 facilitates cell proliferation by ubiquitinating USP49 through binding to its SPRY domain ( Wu et al, 2022a ). In addition, S-phase kinase-associated protein 2 (Skp2) specifically degrades cyclin-dependent kinase inhibitor 1B (CDKN1B) ( Singh et al, 2018 ), and mindbomb homolog 1 (MIB1) enhances the ubiquitin-mediated degradation of suppression of tumorigenicity 7 (ST7) ( Zhang et al, 2021b ); both Skp2 and MIB1 promote tumor proliferation.…”
Section: How E3s and Dubs Influence Various Phenotypes Of Pdacmentioning
confidence: 99%